Students’ Reference Mastery in Narrative Text at XI GRADE of Senior High School - dahliana dahliana dahliana; Muhammad Zaim (UIR Press, 2019)
Reference is an essential component for comprehending a reading text. In comprehending a text some students had problem such as their limited vocabulary, inability to interpret reference, and lack of background knowledge. The purpose of the research was to find out the students’ reference mastery in narrative text and students’ difficulties in mastering reference. This research was a descriptive research. Random sampling technique was applied and twenty two students of XI grade of SMAN 1 Tempuling were taken as the subject of the research. The data were collected through quantitative and qualitative methods. Reading test was distributed to collect quantitative data, while interview was applied to gather qualitative data. The findings of this research reveal that the students’ reference mastery was in good category, but some problems still appeared which were affected by some factors; lack of practice, limited vocabulary mastery, and poor grammar mastery. Thus, it can be concluded that the students’ reference mastery in narrative text needed to be improved.